Subsoil tillage improved the maize stalk lodging resistance under high planting density - Feng, Xueying; Ma, Daling; Lei, Tianen; Hu, Shuping; Yu, Xiaofang; Gao, Julin (Frontiers in Plant Science, 2024)
Lodging reduces the maize yield and quality. The improvement in maize lodging resistance has proven instrumental in maximizing the yield potential of maize varieties under high-density planting. Tillage practices accommodate larger groups enhanced soil conditions by enhancing soil conditions accommodating larger groups. This study aimed to elucidate the impact of subsoil tillage in reducing the maize stalk lodging rate. The maize cultivar Xianyu 335(XY335) and Zhongdan2(ZD2)was selected for field experiments including two tillage methods, shallow rotary (RT) and subsoil (SS), Two maize varieties namely, Xian yu335 (XY335) and Zhong dan 2 (ZD2) were planted atand two different densities i.e., high (75,000 plants ha -1 (D1)) and low (105,000 plants ha -1 (D2)), were set up to investigate and analyse the changes of maize lodging rate and the related indexes of lodging resistance under SS and RT condition. Maize height, ear height, stalk dry matter accumulation, mechanical strength, and lodging rate were studied from the silking stage to the maturity stage. The changes in each index were analyzed under the subsoil and rotary tillage. The findings revealed that under high density, as compared to rotary tillage, subsoil tillage decreased the plant and ear height by 9.01～9.20 cm and 3.50～4.90 cm respectively. The stalk dry matter accumulation was enhanced by 8.98%～ 24.98%, while stalk diameter between 2 ～and 7 internodes increased by 0.47 ～4.15 mm. Stalk cellulose increased by 11.83% ～ 12.38%, hemicellulose increased by 6.7%～15.97%, and lignin increased by 9.86%～15.9%.The rind puncture and crushing strength improved by 3.11～20.06%, and 11.90 ～ 27.07% respectively. The bending strength increased by 6.25 ～ 27.96% whereasand the lodging rate decreased by 1.20～6.04%. Yield increased by 7.58%～8.17%. At subsoil tillage when density increased, the index changes in ZD2 were mostly less than those in XY335. Plant and ear heights were found to be positively correlated with stalk lodging rates. The rind penetration strength, bending strength, crushing strength, stalk diameter, and dry matter accumulation all had a negative correlation with the lodging rate. It suggested that subsoil tillage was beneficial to lodging resistance.